The First report of Nigrospora sphaerica Associated with Heliocarpus americanus Seeds in Brazil - Caliandra Bernardi; Cleverson Busso; Regis Callegaro Borin; Sérgio Miguel Mazaro; Roberto Sadao Sinabucro Saburo (Floresta e Ambiente, 2020)
Abstract Heliocarpus americanus is a fast-growing native tree, excellent for recovering degraded areas and its wood can be used as firewood or in the production of charcoal. For its use it is necessary identify the fungus will cause diseases. This work aimed to make the first report of the occurrence of the fungus Nigrospora sphaerica in seeds of H. americanus in Brazil. The fungus was detected in a batch of seeds collected from the native species. The fungus were analyzed by the Blotter test. Then, the fungus was isolated from the seeds and it characterized by morphology of colony and conidia and, molecular tests, what confirmed the identity of the pathogen. To conclude the study, the Koch’s postulates test was performed, where it was observed its transmission of seeds to H. americanus seedlings, elucidating the fungal damage in the seeds and later seedlings of this species.